Evaluation of The Effect Using Ultrasonic Waves Alone or with The Adjunctive Use of Er:YAG Laser in the Healing of Peri-implant Mucositis. (Randomized Clinical Trial) (Journal of Hama University, 2020)
The aim of the study was to assess the healing of peri-implant mucositis by using ultrasonic mechanical treatment alone or with the adjunctive use of  Er: YAG  laser and to refer which is better.  The sample consisted of 32 patients (98 implants) suffering from peri-implant mucositis with 7≤pockets≤4 the sample is randomly divided into two groups by using split mouth design, the mechanical treatment group received scaling by using carbon tip ultrasonic scaler, while the second group received the same mechanical treatment with adjunctive use of  Er: YAG  laser (ERL). Gingival index GI, pocket depth PD and clinical attachment  level CAL were measured at baseline, 1,3 and 6 months after treatment. The results showed significant differences (p0.05) between the treatment methods during all follow up for GI, CAL and (3-6) months for PD. This study concluded that the effectiveness of the mechanical treatment alone or in combination with the Er: YAG laser in the treatment of peri-implant mucositis, With a better outcomes for mechanical treatment with adjunctive use of  laser.